Bone Stress Injuries Are Associated With Differences in Bone Microarchitecture in Male Professional Soldiers. Issue 12 (26th August 2019) - Schanda, Jakob E.; Kocijan, Roland; Resch, Heinrich; Baierl, Andreas; Feichtinger, Xaver; Mittermayr, Rainer; Plachel, Fabian; Wakolbinger, Robert; Wolff, Klaus; Fialka, Christian; Gruther, Wolfgang; Muschitz, Christian
ABSTRACT: Bone stress injuries are commonly due to repetitive loading, as often described in competitive athletes or military recruits. The underlying pathophysiology of bone stress injuries is multifactorial. The present cross‐sectional study investigated (i) cortical and trabecular bone microstructure as well as volumetric bone mineral density in subjects with bone stress injuries at the tibial diaphysis, measured at the distal tibia and the distal radius by means of high‐resolution peripheral quantitative computed tomography (CT), (ii) areal bone mineral density using dual‐energy X‐ray absorptiometry as well as calcaneal dual X‐ray absorptiometry and laser, and (iii) the influence on bone turnover markers of formation and resorption at the early phase after injury. A total of 26 Caucasian male professional soldiers with post‐training bone stress injury at the tibial diaphysis were included (case group). A total of 50 male, Caucasian professional soldiers from the same military institution served as controls (control group). High‐resolution peripheral quantitative CT revealed a higher total area at the radius within the case group. Cortical bone mineral density was reduced at the radius and tibia within the case group. The trabecular number and trabecular thickness were reduced at the tibia in the case group. The trabecular network was more inhomogeneous at the radius and tibia within the case group. Calcaneal dual X‐ray absorptiometry and laser was significantly reduced in the case group. This study quantified differences in bone microstructure among otherwise healthy individuals. Differences in bone microarchitecture may impair the biomechanical properties by increasing the susceptibility to sustain bone stress injuries. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:2516–2523, 2019